Comparison of Calcium Hydroxidea and Triple Antibiotic Paste on Inter-Appointment Endodontic Pain - Maliha Muneer, Maheen Choudhry, Sunnaeyah Waris, Muhammad Pervaiz Iqbal, Amira Shahid, Faiza Noureen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endodontic pain is related to inflammatory reactions in the tissues correlated to the damage, and the nature of damage. Inter-appointment pain is correlated to the instrumentation, irrigation and all the other procedures done during appointments. Triple antibiotic paste can be more effective intacanal medicament than calcium hydroxide. But there was a need to confirm its effectiveness. Aim: To compare the effect of calcium hydroxide and triple antibiotic on inter-appointment endodontic pain. Methods: This randomized controlled trial was conducted in the Department of Operative Dentistry, PMC Dental Institute, Faisalabad Medical University, Faisalabad for four months. Sixty cases were enrolled by using Non-probability, consecutive sampling and were divided randomly in two groups. In group 1, triple antibiotic paste was placed for inter-appointment pain. In group 2, calcium hydroxide was placed. After one week, pain was observed. Data was analyzed in SPSS 25. Results: In patients who received triple antibiotics paste, the mean age of patients was 36.90±9.49 years. In patients who received calcium hydroxide, the mean age of patients was 34.83±10.32 years. In patients who received triple antibiotics paste, there were 15(50%) males and 15(50%) females. In patients who received calcium hydroxide, there were 16(53.3%) males and 14 (48.7%) females. In patients who received triple antibiotics paste, the mean pain score was 0.90±1.88. In patients who received calcium hydroxide, the mean pain score was 2.83 ± 3.07. In patients who received triple antibiotics paste, there were 6 (20%) patients who had pain while 24(80%) patients did not report about pain. In patients who received calcium hydroxide, there were 15 (50%) patients who had pain while 15(50%) patients did not report about pain. Conclusion: Triple antibiotic paste was found to be more effective in relieving pain than calcium hydroxide. Key words: Calcium hydroxide, triple antibiotic paste, inter-appointment endodontic pain, visual analogue scale